Homology of Normal Chains and Cohomology of Charges - De Pauw, Th; Hardt, R. M.; Pfeffer, W. F. (Memoirs of the American Mathematical Society, 2017)
We consider a category of pairs of compact metric spaces and Lipschitz maps where the pairs satisfy a linearly isoperimetric condition related to the solvability of the Plateau problem with partially free boundary. It includes properly all pairs of compact Lipschitz neighborhood retracts of a large class of Banach spaces. On this category we define homology and cohomology functors with real coefficients which satisfy the Eilenberg-Steenrod axioms, but reflect the